Judicial Review of Administrative Actions in Libya: An Analytical and Critical Study in the Context of the Absence of a Specialized Administrative - Abdulrahman Ahmed Mohamed Alzanati (Journal of Scientific and Human Dimensions, 2025)
This research addresses the critical issue of the absence of a specialized administrative judiciary in Libya and its impact on the effectiveness of judicial oversight over public administration. It analyzes the theoretical foundations of judicial review, examines the current Libyan legal framework, and evaluates the capacity of ordinary courts to adjudicate administrative disputes, highlighting the limitations caused by the lack of specialization and procedural adaptation.The study explores the negative consequences of this absence, including weak oversight of technical or discretionary administrative decisions, lengthy litigation procedures, and declining public trust in administrative justice. A comparative analysis of successful Arab models such as Egypt, Tunisia, Morocco, and Algeria provide valuable insights into adaptable structures for the Libyan context.Based on these findings, the research proposes a legal and institutional framework for establishing an independent administrative judiciary in Libya, tailored to national specificities and aimed at strengthening the rule of law, protecting individual rights, and building effective legal institutions aligned with modern governance standards.
Keywords: Administrative judiciary; Judicial review; Administrative legitimacy; Administrative disputes; Ordinary judiciary